On Question of Representation of Intra-company Written Communication in Foreign Language Professionally-Oriented Textbook for Undergraduate Students of Engineering Specialty - E. V. Rybakova (Научный диалог)
The article is devoted to the usefulness of including the exercises based on texts of intra-company written communication in a professionally-oriented textbook for undergraduate students of engineering specialty. The issues associated with the methodological potential of exercises, designed on the basis of this texts, are discussed in terms of the most complete implementation of conditions to ensure the communicative orientation of the textbook and the principles of contextual learning. The possibility of using some of the functions of intra-company communication texts, such as organising and regulatory functions, as a way of structuring communicative activities in the manual is proved. The author argues that it provides a context-due alternation of oral and written communication and representation of the types of discourse key for the manual. It is demonstrated that this approach is more effective when creating the training model of professional activity in each section of the manual where the exercises, designed on the basis of intra-company emails and documents, carry out the deployment professional of the plot, adjust the consistency of the presentation of professional situations involving oral and written communication. Possibility of use of exercises, designed on the basis of reports to optimize preparation for the study of texts representing scientific discourse is considered, since reports have a number of similar functional and stylistic characteristics with scientific articles.